GIANT PLEOMORPHIC ADENOMA OF THE SALIVARY GLAND - CASE REPORT - Constantin MIHAI; Cristian BUDACU; Iulia CHISCOP (Romanian Dental Association for Education, 2014)
Salivary gland pathology is a main issue in maxillofacial surgery. Pleomorphic adenoma or mixed tumor is the most common type of salivary gland tumor, representing almost two thirds, 85% involving parotid gland. This benign tumor with slow and continous, asymptomatic growth can sometimes reach an enormous size. Practitioners must consider the semnificative risk of malignant transformation, especially in tumors with long time evolution, and also the possibility of postoperative recurrence. We present a case of giant pleomorphic adenoma of the parotid gland in a 92-year-old woman with a history of more than 20 years. Clinical examination revealed a giant mass on the right side of the face, without any signs of facial nerve damage. The tumor was completely removed by total parotidectomy and preservation of the facial nerve. The tumor measured 15/9/8 cm and weighed 530 g. Histopathologic examination showed a predominat myoepithelial component and schwanom-like areas and no evidence of malignant transformation. Postoperative evolution was favorable, with excellent functional and aesthetic results.